The Quechua names of Viracocha, supposed "Creator God" of the evangelizers - Duviols, Pierre (1977)
Colonial written sources are full of data on Viracocha, but these data often seem contradictory. They are, more than because of the right to information, because of the misinterpretation on the part of the authors of the chronicles and post-Inca relationships. For this reason, the first step of the investigation must consist of stripping that famous divinity of the Christian disguise that the missionaries and the chroniclers put on him. For this we will ask ourselves: Why did the missionaries want to make Viracocha a creator god? And how did they make him a creator god? We find the answer to the first question by analyzing the ideological and theological tendencies of missionary Spain in the 16th century. The answer to the second question is in the same chronicles.